Blended Learning in Brunei’s Preschool Education: Innovations, Challenges, and Policy Implications - Siti Noorhanida Md Yussof (SEAMEO CECCEP, 2025)
Blended learning, which combines face-to-face and online instruction, gained prominence globally during the COVID-19 pandemic as education systems sought continuity amid school closures. In Brunei Darussalam, blended approaches were introduced across all levels of education, including preschool, where play-based learning and parental involvement are central. However, despite growing adoption, there remains limited literature examining the role, challenges, and developmental appropriateness of blended learning in early childhood education (ECE). This article reviews and analyses existing research, policy documents, and contextual reports related to blended learning in Brunei’s preschool sector, situating the discussion within national priorities such as Wawasan 2035 and the Sistem Pendidikan Negara Abad ke-21 (SPN21). The review identifies innovative practices, including digital storybooks, video-based lessons, interactive home activities, and the use of television and radio programmes to support learning continuity. It also highlights key challenges, such as unequal access to technology, varying parental capacity, limited teacher preparedness for digital pedagogy, and concerns about screen time and child well-being. The analysis suggests that blended learning can enrich preschool education when it is developmentally appropriate, play-oriented, and supported by adults, but it should function as a complement rather than a substitute for face-to-face learning. Policy implications emphasise investment in infrastructure, teacher professional development, and structured parental support to ensure equitable and sustainable implementation.